Developmental Change in Sibling Support and School Commitment Across Adolescence. (28th December 2017) - Rogers, Christina R.; Guyer, Amanda E.; Nishina, Adrienne; Conger, Katherine J.
Abstract : School commitment typically declines across adolescence, but the family‐level factors that explain this decline have not been fully characterized. This study investigated sibling support as a family resource in predicting school commitment across 7th–10th grade using a sample of 444 adolescents ( M ages  = 12.61, 13.59, 14.59, 15.58 years). Results showed that sibling support linearly increased and school commitment decreased and stabilized, independently, over time. Sibling support positively predicted school commitment in seventh grade and across time, suggesting that having supportive siblings may help to offset adolescents' declines in school commitment. Furthermore, having a brother enhanced this association versus having a sister. These findings provide insight into ways to help youth maintain school commitment across the middle‐ to high school transition.